2009
DOI: 10.1039/b910378c
|View full text |Cite
|
Sign up to set email alerts
|

The commensurate modulated structure of the metastable state in spin crossover complex [Fe(abpt)2(NCS)2]

Abstract: Two new polymorphs (C and D) of [t-Fe(abpt)(2)(NCS)(2)] are characterized, a commensurate modulated structure with the c axis tripled in the thermally quenched metastable high spin state at 25 K is found in polymorph C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 41 publications
1
18
1
Order By: Relevance
“…Fe1 moves with respect to Fe2 by about 0.1 along a, 0.08 along b, and 0.15 along c. Such structural instability has also been reported for other compounds, for which the modulated location of metastable HS molecules at low temperature yielded a triplicate cell parameter. [26] Spin-state ordering of the INT phase: The most unusual behavior of the present compound is the appearance of a complex structure in the intermediate phase corresponding to the partial SC at the approximately 100 K centered plateau. This new phase results from a symmetry breaking among crystallographically equivalent cation sites.…”
Section: The Chemical Composition and Purity Of [Fementioning
confidence: 91%
See 1 more Smart Citation
“…Fe1 moves with respect to Fe2 by about 0.1 along a, 0.08 along b, and 0.15 along c. Such structural instability has also been reported for other compounds, for which the modulated location of metastable HS molecules at low temperature yielded a triplicate cell parameter. [26] Spin-state ordering of the INT phase: The most unusual behavior of the present compound is the appearance of a complex structure in the intermediate phase corresponding to the partial SC at the approximately 100 K centered plateau. This new phase results from a symmetry breaking among crystallographically equivalent cation sites.…”
Section: The Chemical Composition and Purity Of [Fementioning
confidence: 91%
“…From a physical viewpoint, this ordering phenomenon of molecular spin-states in an INT phase is very different from the case of compounds with crystallographically independent sites, which may display different thermal behavior and different HS populations without symmetry breaking. [26,27] Phase diagram and symmetry-breaking order parameters: When the cell translational symmetry changes to (a, 5b, 3c), at least two symmetry-breaking order parameters (OP), which do not transform according to the same irreducible representation, have to be involved. For example, one (h) may be associated with the cell triplication along c and the other (x) with the cell quintuplication along b.…”
Section: The Chemical Composition and Purity Of [Fementioning
confidence: 99%
“…It may give rise to hysteretic response under the effect of control parameter such as temperature (LITH, light-induced thermal hysteresis), 28 pressure (LIPH, light-induced pressure hysteresis), 29 or light excitation density (LIOH, light-induced optical hysteresis). 30,31 There are few SCO crystals for which the spin crossover is associated with symmetry breaking at thermal equilibrium [32][33][34][35] or in the photoinduced state ( [36][37][38] and references therein). For most of the SCO systems, the spin-state switching occurs in one step without any symmetry change, as it is the case for the two polymorphs studied here.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is trans-[Fe(abpt) 2 (NCS) 2 ]. This compound exists in four different polymorphs (A, B, C and D), all of them presenting different magnetic behaviours [5,6]. For polymorph D, it was shown that a light induced excited spin state trapping could be achieved since light excitation could change the Fe low-spin to a high-spin state at 50 K [5].…”
Section: Introductionmentioning
confidence: 99%